As faces e os disfarces da informalidade no capitalismo contemporâneo: um estudo do comércio de rua em Pau dos Ferros/RN - Silva, Franciclézia de Sousa Barreto (2011)
This paper discusses the expression of informality in contemporary capitalism. Thematic of relevance to the analysis of the reality of work today and the logic that moves the capital, its real presence in the lives of individuals. The street trading of Pau dos Ferros town, popularly known as "street market" was chosen as the search space. The main objective is to seize and examine the articulations and logic, present in the configuration of the street trading of this city, located in the state of Rio Grande do Norte, explaining the functionality of informality for capitalist accumulation, but also for the reproduction of segments of the working class. Our analysis is based in the perspective of totality, trying to grasp the historical determinations of the phenomenon in focus. It includes the analysis of the mechanisms used by the capital to reproduce itself in the current historical context, which has been implicated in the composition of the labor markets of different countries and in various forms of exploitation to which workers in general are subject. It also means discussing the development of capitalism in Brazil, the logic that permeates its dependence, and especially the use of over-exploitation of labor, as a lever for internal accumulation. The course of investigation consisted of theoretical research to form the basis of theoretical and methodological analysis and to outline the context in which our research object is inserted, and field research conducted in two phases: systematic observation, which allowed to map traders features and the infrastructure of commerce, and the conduction of interviews with key informants. The material collected was scrutinized according to analytical scheme inspired by the content analysis. Among the main considerations developed from the research process we include: the street trading of Pau dos Ferros remains shrouded in the majority sale of agricultural products, this demonstrates the structural characteristics of the region. However, the supply of this product is no longer restricted to the excess of small local producers. The presence of the dealer changed the distribution of the product, streamlining it. In parallel, business practices are developed, practices in which traded goods (industrial) reflect the moment of capitalist restoration, a larger business network. The reflections also made it possible to show that street trading follows developing on the basis of informal work, which gains functionality to the system, as it is configured as a space commonly used to drain part of the production, of industries (clothing/shoes), especially if the distribution is considered as an essential element of the complex process that aims at capital appreciation. This activity has been functioning as a place of employment and income generation for the subjects who are away from formal employment, masking, this way, unemployment, moreover, they allow them to continue as consumers. Such expressions reflect the ability and the logic of capital to expand and aggregate into so many realities. It is underway today, the logic that has led many workers to join the project of domination of capital, by the illusory chance to become capitalists. The aim has been to turn the subject into a consumer and the worker an enterprising